Putusan Kumulasi Cerai Gugat Dan Itsbat Nikah Perspektif Istihsan Bi al-Mashlahah (Studi Putusan Nomor 452/Pdt.G/2022/PA.Bkt) - Firdaus, Zulkifli (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2025)
The Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law in Indonesia have regulated the implementation of marriage. These provisions regulate legal marriage according to sharia, and must also be recorded by the Marriage Registration Officer of the local Religious Affairs Office. The existence of underhand / siri marriages in Islamic societies in Indonesia sometimes causes legal problems when there is a divorce in the Religious Court due to the absence of a marriage certificate. This study aims to analyze the istihsan bi al-mashlahah method which is one of the considerations of the Bukittinggi Religious Court Judge in Decision Number 452/Pdt.G/2022/PA.Bkt. The verdict granted a cumulative itsbat nikah divorce suit, but the marriage did not meet the statutory provisions and the Compilation of Islamic Law in Indonesia. The method in this research is a normative legal study with a case approach. Primary data is sourced from the Bukittinggi Religious Court Decision Number 452/Pdt.G/2022/PA.Bkt. The conclusion of this research is that the istihsan bi al-mashlahah method used by the judge in order to provide a solution by granting itsbat nikah solely for the divorce process of the plaintiff and the defendant, because of the benefit aspects that will be achieved, namely maintaining the soul (hifz al-nafs) and maintaining offspring (hifz al-nasl).